Spelling Intervention Reimagined: Enhancing Grade 6 Students’ Spelling Literacy through Tactile, Digital, and Phonetic Strategies - Orozco, Mary Eugenie Joy (Journal of Interdisciplinary Perspectives, 2025)
This study provides a novel comparative analysis of tactile, digital, and phonetic strategies among Grade Six students, highlighting the superior performance of phonetic methods while offering actionable insights into the specific benefits and challenges associated with each approach. Employing a counterbalanced quasi-experimental design to three different groups with a total of 200 students through complete enumeration, the study reveals that students’ exposure to the phonetic strategy was found to be most effective, which resulted in Outstanding performance, while the digital strategy resulted in Satisfactory performance, and tactile strategy yielded a Fairly Satisfactory performance. The phonetic strategy resulted in significant differences in students' mean spelling scores (p < 0.001). Highlights for tactile strategy include the fun factor in gamification, which enhances effectiveness due to ease of manipulation. In contrast, digital strategy incorporates the fun factor in gamification to aid in remembering, provides a helpful challenge, and motivates users through a ranking system. Phonetic strategy, meanwhile, involves chunking words based on syllables, which enhances the effectiveness of learning a word and offers the flexibility to divide words. Lowlights for tactile strategy include difficulty in finding the letters, limited number of letters, and level of difficulty, while for digital strategy include random tapping or placement of letters, technical issues, and anagrammatic words, and for phonetic strategy include single or multiple syllables, level of difficulty, and effectivity silent or double letters. It is recommended that grade school teachers, especially in the grade six level who are teaching spelling, should look into the dynamics of these three strategies in terms of performance results, highlights, and lowlights in contextualizing instructions, as well as considering the mixture of all three strategies rather one focusing only on one to address the varied needs of the students. Further, this paper recommends the conduct of parallel studies in other grade levels or public schools to compare results and to have a better viewpoint of the topic being studied.